The MIREN Road Survey Database: Standardized Vegetation Sampling to Advance Our Understanding of Biodiversity Responses in Mountain Systems Across the Globe - Sylvia Haider; Jonas J. Lembrechts; Jake Alexander; Vincent Ralph Clark; Lisa J. Rew; Meike Buhaly; Marc Achermann; Alla Aleksanyan; Alisa Alvarez; Marco Andrello; José R. Arévalo; Valeria Aschero; et al. (Global Ecology and Biogeography, 2026)
Motivation The database initiated by the Mountain Invasion Research Network (MIREN) is one of the few globally implemented standardized vegetation surveys in mountains. The focus is on collecting plant species occurrences at 5‐year intervals along and adjacent to mountain roads spanning elevational gradients, with the goal of providing critical information about the ongoing spread of non‐native plants and the potential impacts of climate and human‐caused disturbance in the form of road infrastructure on mountain vegetation. Main Types of Variables Contained To date, the database contains almost 170,000 georeferenced records of plant species. Overall, 6854 vascular plant species were observed in 3364 plots across 25 regions, with many of these plots being revisited every 5 years. Each plot is identified by its coordinates, elevation and distance to the road. The status of each individual species (native, non‐native or unknown) is determined in accordance with regional databases. Spatial Location and Grain Plant species were surveyed at 20 sample sites, placed at regular elevational intervals along each mountain road, with typically three roads selected per region. Each sample site is subdivided into three 2 m × 50 m plots, one parallel to the road and two perpendicular to it, extending into adjacent vegetation. The 25 studied regions cover all continents except Antarctica. Time Period and Grain Data were collected between 2007 and 2023, with surveys being repeated at 5‐year intervals in a subset of regions. Three regions include four time‐steps, while seven and three regions were sampled three times or twice, respectively. In most regions, long‐term monitoring is ongoing. Major Taxa and Level of Measurement All vascular plant species. Software Format Data are available through a .csv file on Zenodo ( https://doi.org/10.5281/zenodo.15749536 ).

Thermophilization: Concepts, Methods, and Implications of Changes in Community Composition due to Global Warming - Kenneth J. Feeley; Evelin Iseli; Billur Bektaş; Rubén D. Manzanedo; Crystal H. McMichael; Jake M. Alexander; Janneke Hille Ris Lambers (Global Change Biology, 2026)
With global warming, many species will shift their geographic ranges coldward (i.e., towards higher latitudes and elevations) to remain within suitable thermal conditions. At the community level, these range shifts result in “thermophilization”—the increasing relative abundance of warm‐adapted (“thermophilic”) species and the concomitant decrease of cold‐adapted species over time. Quantifying rates of thermophilization provides a powerful approach to assessing responses to rising temperatures at the community level, particularly in high‐diversity systems where the detailed spatial data needed to calculate species‐level responses to warming for thousands of individual species are often unavailable. This review synthesizes our current understanding of thermophilization across terrestrial, marine, and aquatic systems. We detail the most common methods used to quantify thermophilization, primarily through the calculation of the Community Temperature Index (CTI, °C), which aggregates species' thermal affiliations into a single community‐level metric that can then be tracked through time to calculate an annualized thermophilization rate (TR, °C year −1 ). We evaluate the advantages of this approach, such as its ability to partition the contributions of underlying demographic processes (i.e., recruitment vs. growth vs. mortality, or colonization vs. extinction) and/or individual species and species groups, its flexibility in using diverse data sources like herbarium records and citizen science, and its ability to test relationships between TR and site‐specific conditions such as elevation, landcover, and anthropogenic disturbances. We also discuss some of the standing challenges and limitations of the thermophilization approach, including a lack of standardization that hinders large‐scale synthetic analyses, the challenge of propagating estimation errors from the species‐ to community‐level, and difficulties in interpreting and communicating results. We then discuss the implications of thermophilization for ecosystem stability and function, including the potential for biodiversity losses and altered ecosystem services. Finally, we highlight several important and exciting avenues for future research on climate‐driven shifts in community composition.

Collaborating across mountains: contributions of the Mountain Invasion Research Network (MIREN) to ecology and conservation - Aníbal Pauchard; Eduardo Fuentes-Lillo; Jake Alexander; Manzoor A. Shah; Agustina Barros; Lohengrin Cavieres; Sylvia Haider; Jonas J. Lembrechts; Keith McDougall; John W. Morgan; Vincent Ralph Clark; Irfan Rashid; et al. (Biological Invasions, 2026)

Correction: Positive and negative plant–plant interactions influence seedling establishment at both high and low elevations - Chantal M. Hischier; Janneke Hille Ris Lambers; Evelin Iseli; Jake M. Alexander (Alpine Botany, 2026)

Variation in the effectiveness of nonnative plant removal along elevation gradients in Switzerland - Georg V. Flückiger; Sascha Gregori; Jake M. Alexander (Alpine Botany, 2026)
Limiting the spread and impact of nonnative species in mountain ecosystems is a key management objective. While current management strategies may be tailored to species traits and life histories, understanding how management effectiveness varies along elevation gradients could help optimize control measures and ultimately support native plant communities. We hypothesized that management efficiency would increase with elevation due to smaller population sizes and more limiting environmental conditions affecting population performance near range edges. To test our hypothesis, we conducted a removal experiment with two perennial ( Solidago canadensis and Lupinus polyphyllus ) and one annual ( Erigeron annuus ) invasive species in the eastern Swiss Alps. Control effectiveness (recovery of plant cover after 1 year) depended on plant life history, with a strong reduction in cover for the perennial species. However, elevation did not significantly affect short-term management outcomes, suggesting consistent efficiency of control measures across the gradient. A germination experiment using soil samples from field sites revealed higher seedling numbers for the annual species and a decline in emergence with elevation for both focal species analyzed, suggesting that seed bank size may influence management outcomes. Based on our findings, we recommend long-term strategies that include the sowing of native seed mixtures to support recovery. Additionally, lower germination at higher elevations suggests that removal success may eventually be greater at species’ upper range limits. Overall, our study shows that considering elevation-related variation can help refine nonnative plant management strategies in mountains.

Mountain Roads Across the Globe Significantly Alter Local Soil Thermal Microclimates - Renée Lejeune; Eduardo Fuentes‐Lillo; Jake Alexander; Romina D. Dimarco; Stef Haesen; Sylvia Haider; Lore Hostens; Anke Jentsch; Josef Kutlvašr; Jonathan Lenoir; Martin A. Nuñez; Aníbal Pauchard; et al. (Global Ecology and Biogeography, 2026)
Aim Mountain roads host plant communities that differ strongly from the adjacent natural vegetation. Besides the effect of propagule pressure, altered disturbance and soil processes, one of the reasons given for the strong influence of mountain roads on species distributions is a significantly altered soil thermal microclimate in the roadside compared to the adjacent vegetation, as a direct consequence of road disturbance. However, the thermal microclimatic differences between roadside and natural vegetation have rarely been quantified, particularly across large spatial extents. This study provides the first global quantification of roadside soil temperature patterns along elevational gradients. Location Mountain roads in eight mountain regions from the Mountain Invasion Research Network (MIREN): Argentina, Chile, Czech Republic, Norway, Spain (Tenerife and La Palma), Switzerland, and the USA. Methods In this study, we analysed in situ measured topsoil temperatures ( Results Across most regions, roadside soils exhibited consistently warmer maxima (3.62°C ± 2.61°C) and colder minima (1.39°C ± 1.40°C) than soils in adjacent vegetation. Although temperature distributions between roadside and natural habitats largely overlapped, these systematic shifts indicate increased thermal variability and higher frost risk in roadside environments. Main Conclusions Roadsides create distinct thermal microhabitats even within heterogeneous mountain landscapes. These altered temperature regimes, particularly when combined with vegetation structure and other environmental factors such as soil moisture, may influence plant performance and distribution. Our findings highlight the ecological relevance of thermal microclimates in understanding biodiversity patterns along mountain roads.

Shifts in High Arctic tundra vegetation structure linked to variation in soil conditions - Jana Ruethers; Lena Bakker; Sebastian Doetterl; Simone Fior; Jamila Gisler; Cara Magnabosco; Annina Maier; Moritz Mainka; Kristine Bakke Westergaard; Jake Alexander (Polar Biology, 2026)

Individual recognition in guppies does not require large brains - Gilles De Meester; Dylan Brimaud; Markus Wollin; Jake M. Martin; Alexander Kotrschal; John L. Fitzpatrick; Niclas Kolm (Behavioral Ecology and Sociobiology, 2025)
It is often assumed that group-living animals require larger brains in order to deal with the various social challenges they encounter. One such key challenge is the need to recognize and discriminate between specific group members. Individual recognition is often deemed the most cognitively demanding form of recognition. Hence, one could expect this ability to be facilitated by the evolution of larger brains. So far, this hypothesis remains largely untested. In this study, we investigated the link between relative brain size and individual recognition, using Trinidadian guppies ( Poecilia reticulata ) from artificial selection lines for either increased or decreased relative brain size. In a first experiment, we compared the selection lines in their ability to spontaneously discriminate between a familiar and unfamiliar conspecific. In a second experiment, we actively trained guppies from the selection lines to associate a particular individual with the presence of food. Overall, we found evidence for individual recognition, confirming earlier research on this species. However, individual recognition was independent of brain size selection regime in both experiments. Guppies spontaneously recognized and preferably associated with a familiar individual. In the trained association experiment, however, fish showed no preference for either stimulus fish. Our study suggests that although small fishes like the guppy are capable of individual recognition, larger brains do not necessarily facilitate this ability. Our study demonstrates that to fully understand the link between sociality and cognition, one needs to verify which exact social challenges require the evolution of larger brains. Significance statement Living in a group is a complex challenge, and is thus said to require relatively large brains. Despite this assumption, there is very little known about which particular aspects of group-living are actually cognitively demanding to a degree that they require a higher investment in brain tissue. Here, we tested the specific hypothesis that the ability to recognize and remember specific individuals, i.e. individual recognition, a keystone of sociality, is cognitively challenging by comparing guppies with known differences in relative brain size in their ability to recognize a familiar shoal-member and learn the difference between two new individuals. Although guppies demonstrated individual recognition, relative brain size did not affect their performance. Our results provide valuable insights in the evolution of sociality and its link with relative brain size.

Global Homogenisation of Plant Communities Along Mountain Roads by Non‐Native Species Despite Mixed Effects at Smaller Scales - Meike Buhaly; Jake M. Alexander; Aníbal Pauchard; Lisa J. Rew; Tim Seipel; José Ramón Arévalo; Valeria Aschero; Joshua P. Averett; Agustina Barros; Lohengrin A. Cavieres; V. Ralph Clark; Curtis C. Daehler; et al. (Global Ecology and Biogeography, 2025)
Aim Mountain ecosystems are experiencing increased invasion of non‐native plants. These increases in non‐native species put mountains at risk of biotic homogenisation and a reduction of biodiversity. Our study aims to test if non‐native plant species are contributing to biotic homogenisation along roadways in mountain regions and how this changes along elevation gradients and across spatial scales. Location 18 globally distributed mountain regions. Time Period 2012–2023. Major Taxa Studied Vascular plants. Methods We used standardised vegetation surveys including species cover from 18 mountain regions worldwide to analyse whether the addition of non‐native species to the native flora increased or decreased Bray–Curtis dissimilarity (i.e., beta‐diversity) among roadside plant communities along elevation gradients ranging from 15 to 3919 m a.s.l. We tested this at the local, regional, continental and global scales using mixed‐effects models and confirmed it using null models. Results In the New World, we mainly observed homogenisation across regions and scales, as beta‐diversity was mostly lower with the addition of non‐native species. This was particularly true for low elevations. In contrast, we predominantly found community differentiation in the Old World, specifically at smaller (i.e., local and regional) scales. At the global scale, communities became more similar through the addition of non‐native species at all elevations. Main Conclusions Large‐scale homogenisation might be interpreted as a signal that high‐elevation plant communities along roadways may become more similar as non‐native species continue to spread upwards. Future studies should investigate the mechanisms driving the observed patterns of both homogenisation and differentiation by non‐native species, and explore the potential consequences of these patterns for ecosystem function and resilience.

Utilizing national wastewater and sales data to derive and validate the correction factors of five common antidepressants for wastewater-based epidemiology - Zeyang Zhao; Jingyi Yuan; Qiuda Zheng; Benjamin J. Tscharke; Tim Boogaerts; Zhe Wang; Shuo Chen; Jake W. O'Brien; Alexander L.N. van Nuijs; Adrian Covaci; Jochen Mueller; Phong K. Thai (Water Research, 2025)

Snow Height Sensors Reveal Phenological Advance in Alpine Grasslands - Michael Zehnder; Beat Pfund; Jan Svoboda; Christoph Marty; Yann Vitasse; Jake Alexander; Janneke Hille Ris Lambers; Christian Rixen (Global Change Biology, 2025)
Long‐term phenological data in alpine regions are often limited to a few locations and thus, little is known about climate‐change‐induced plant phenological shifts above the treeline. Because plant growth initiation in seasonally snow‐covered regions is largely driven by snowmelt timing and local temperature, it is essential to simultaneously track phenological shifts, snowmelt, and near‐ground temperatures. In this study, we make use of ultrasonic snow height sensors installed at climate stations in the Swiss Alps to reveal the phenological advance of grassland ecosystems and relate them to climatic changes over 25 years (1998–2023). When snow is absent, these snow height sensors additionally provide information on plant growth at a uniquely fine temporal scale. We applied a two‐step machine learning algorithm to separate snow‐ from plant‐height measurements, allowing us to determine melt‐out for 122 stations between 1560 and 2950 m a.s.l., and to extract seasonal plant growth signals for a subset of 40 stations used for phenological analyses. We identified the start of growth and calculated temperature trends, focusing particularly on thermal conditions between melt‐out and growth initiation. We observed an advance of green‐up by −2.4 days/decade coinciding with strong warming of up to +0.8°C/decade. Although the timing of snowmelt has not changed significantly over the study period in this focal region, phenological responses to early melt‐out years varied due to differing influences of photoperiodic and thermal constraints, which were not equally important across elevations and communities. Phenological shifts of alpine grasslands are thus likely to become even more pronounced if snowmelt timing advances in the future as predicted. As climate change continues to reshape mountain ecosystems, understanding the interplay between phenological changes and species turnover will be essential for predicting future biodiversity patterns and informing conservation strategies in alpine regions.

Genomic Signatures of Adaptation Across a Precipitation Gradient From Niche Centre to Niche Edge - Samantha Van Deurs; Oliver Reutimann; Hirzi Luqman; Dikla Lifshitz; Einav Mayzlish‐Gati; Jake Alexander; Simone Fior (Molecular Ecology, 2025)
Evaluating the potential for species to adapt to changing climates relies on understanding current patterns of adaptive variation and selection, which might vary in intensity across a species' niche, hence affecting our inference of where adaptation might be most important in the future. Here, we investigate the genetic basis of adaptation in Lactuca serriola along a steep precipitation gradient in Israel approaching the species' arid niche limit and use candidate loci to inform predictions of its past and future adaptive evolution. Environmental association analyses combined with generalised dissimilarity models revealed 108 candidate genes showing nonlinear shifts in allele frequencies across the gradient, with 66% of these genes under strong selection near the dry niche edge. We detected selection acting on genes with separate suites of biological functions, specifically related to phenology and responses to environmental stressors, including osmotic stress, at the dry niche edge, and related to biotic interactions and defence closer to the niche centre. The adaptive genetic composition of populations, as inferred through polygenic risk scores, point to intensified selection operating towards the dry niche edge. However, inference of past and future evolutionary change predicts larger adaptive shifts occurring in the mesic part of the range, which is most affected by climate change. Our study reveals that adaptive shifts in response to climate change can be heterogeneous across a species' range and not necessarily strongest near its niche edge.

Functional Traits Predict Outcomes of Current and Novel Competition Under Warmer Climate - Shengman Lyu; Jake M. Alexander (Global Change Biology, 2024)
Functional traits offer a potential avenue to generalize and forecast the impacts of changing competition on plant communities, including changing outcomes of competition among species that currently interact (current competition) or that will interact in the future following range shifts (novel competition). However, it remains unclear how well traits explain variation in the outcomes of current and novel competition as well as the underlying processes determining coexistence or competitive exclusion, under changing climate. Here, we interacted pairs of high and low‐elevation species in three sites across an elevation gradient in the Swiss Alps. For each species pair, we quantified the population‐level outcomes of competition (invasion growth rates), relative fitness differences, and niche overlap and related these to 15 functional traits that were measured in each site. Most traits were significantly associated with invasion growth rates at the low elevation, where species had greater relative fitness differences, but these associations were much weaker towards higher elevations. This appears to be because traits, particularly those associated with light competition, captured species' relative fitness differences at lower elevations, but not at the high elevation site, highlighting that the predictive ability of traits can depend on environmental context. The amplified relative fitness differences towards lower elevations suggest that climate warming may increase the likelihood of competitive exclusion. In addition, novel competitors tended to show greater niche overlap than current competitors, leading to stronger overall competitive effects. However, in general, trait differences predicted competitive outcomes of novel and current competitors similarly well, suggesting that traits can predict interactions between species that do not yet interact. Our study reinforces the importance of considering changing interactions for predicting species responses to climate change and provides experimental evidence supporting the usefulness of functional trait differences in forecasting the impacts of future plant interactions under changing climate.

Urinary metabolite concentrations of phthalate and plasticizers in infancy and childhood in the UNC baby connectome project - Jake E. Thistle; Chih-Wei Liu; Julia E. Rager; Alison B. Singer; Dazhe Chen; Cherrel K. Manley; Joseph Piven; John H. Gilmore; Alexander P. Keil; Anne P. Starling; Hongtu Zhu; Weili Lin; et al. (Environmental Research, 2024)

Effects of climate change on plant-pollinator interactions and its multitrophic consequences - Judith Trunschke; Robert R. Junker; Gaku Kudo; Jake M. Alexander; Sarah K. Richman; Irene Till-Bottraud (Alpine Botany, 2024)
There is wide consensus that climate change will seriously impact flowering plants and their pollinators. Shifts in flowering phenology and insect emergence as well as changes in the functional traits involved can cause alterations in plant-pollinator interactions, pollination success and plant reproductive output. Effects of rising temperatures, advanced snowmelt and altered precipitation patterns are expected to be particularly severe in alpine habitats due to the constrained season and upper range margins. Yet, our understanding of the magnitude and consequences of such changes in life history events and functional diversity in high elevation environments is incomplete. This special issue collects novel insights into the effects of climate change on plant-pollinator interactions in individual plant species and on network structure of entire plant and pollinator communities in alpine ecosystems. Using simulated changes of earlier snowmelt, natural gradients of variation in temperature, precipitation and snowmelt, or a long-term monitoring approach, these studies illustrate how plant species, plant communities, and pollinators respond to variation in environmental conditions associated with scenarios of ongoing climate change. The collection of papers presented here clearly demonstrates how spatial or temporal variation in the environmental climatic context affects flower abundances and plant community composition, and the consequences of these changes for pollinator visitation, pollination network structure, pollen transfer dynamics, or seed production. As changes in the availability of flowers, fruits, and seeds are likely to impact on other trophic levels, the time is ripe and pressing for a holistic multitrophic view of the effects of climate change on biotic interactions in alpine ecological communities.

Use of consumer insights to inform behavior change interventions aimed at illegal pet turtle trade in China - Wuji Zheng; Anita Kar Yan Wan; Zhan Chen; Alexander Clark; Caitlin Court; Yuanlu Gu; Toby Park; Jake Reynolds; Xiaoxi Zhang; Lishu Li; Tien Ming Lee (Conservation Biology, 2024)
Illegal poaching and overexploitation for the international pet trade are among the greatest threats to freshwater turtles in Southeast Asia. Expanding consumer research in China is crucial to filling knowledge gaps about the scale and structure of illegal trade and developing audience‐targeted and relevant interventions that may reduce demand for illegal turtles as pets. We applied mixed methods to provide a detailed understanding of the consumer side of the illegal pet turtle trade in China. We conducted 30 interviews with key stakeholders and online surveys ( n = 2456) of turtle keepers via community forums. From these, we identified 3 core consumer groups based on their prior turtle‐keeping experience, species exposure, and potential for future purchases. We conducted a thematic qualitative analysis of concepts related to the capability, opportunity, motivation, and behavior (COM‐B) model to determine the factors influencing the illegal pet turtle trade and to identify barriers to illegal purchases. Specifically, we identified purchasers’ capabilities, opportunities, and motivations in the context of legality, enforcement risk, captive breeding, and impacts on wild population. We developed consumer journey maps (i.e., visual representations of customer's experiences throughout their buying journey) for core consumer groups. These maps illustrate the sequential behaviors and processes that consumers undertake when purchasing turtles, from initial exposure to sourcing, keeping, and providing a new home. Key factors influencing illegal purchases included convenient purchase channels, misguided cognition and motivations for pet keeping, and weak law enforcement. Effective interventions included messages focusing on shifting cognition and beliefs, increasing legal risk perception, and emphasizing stringent law enforcement, primarily delivered through online channels. Our results underscore the necessity for adaptable, audience‐tailored interventions to reduce consumer demand for illegal wildlife products. The mixed‐methods approach, combining quantitative and qualitative data, provided a comprehensive understanding of the target behavior and can inform the development of effective intervention strategies.

Effecting change in ecology - Jake M. Alexander (Trends in Ecology & Evolution, 2024)

Positive and negative plant−plant interactions influence seedling establishment at both high and low elevations - Chantal M. Hischier; Janneke Hille Ris Lambers; Evelin Iseli; Jake M. Alexander (Alpine Botany, 2024)
Deciphering how plants interact with each other across environmental gradients is important to understand plant community assembly, as well as potential future plant responses to environmental change. Plant − plant interactions are expected to shift from predominantly negative (i.e. competition) to predominantly positive (i.e. facilitation) along gradients of environmental severity. However, most experiments examine the net effects of interactions by growing plants in either the presence or absence of neighbours, thereby neglecting the interplay of both negative and positive effects acting simultaneously within communities. To partially unravel these effects, we tested how the seedling establishment of 10 mountain grassland plants varied in the presence versus absence of plant communities at two sites along an elevation gradient. We created a third experimental treatment (using plastic plant mats to mimic surrounding vegetation) that retained the main hypothesised benefits of plant neighbours (microsite amelioration), while reducing a key negative effect (competition for soil resources). In contrast to our expectations, we found evidence for net positive effects of vegetation at the low elevation site, and net negative effects at the high elevation site. Interestingly, the negative effects of plant neighbours at high elevation were driven by high establishment rates of low elevation grasses in bare soil plots. At both sites, establishment rates were highest in artificial vegetation (after excluding two low elevation grasses at the high elevation site), indicating that positive effects of above-ground vegetation are partially offset by their negative effects. Our results demonstrate that both competition and facilitation act jointly to affect community structure across environmental gradients, while emphasising that competition can be strong also at higher elevations in temperate mountain regions. Consequently, plant − plant interactions are likely to influence the establishment of new, and persistence of resident, species in mountain plant communities as environments change.

Potential sources of time lags in calibrating species distribution models - Franz Essl; Adrián García‐Rodríguez; Bernd Lenzner; Jake M. Alexander; César Capinha; Pierre Gaüzère; Antoine Guisan; Ingolf Kühn; Jonathan Lenoir; David M. Richardson; Sabine B. Rumpf; Jens‐Christian Svenning; et al. (Journal of Biogeography, 2024)
The Anthropocene is characterized by a rapid pace of environmental change and is causing a multitude of biotic responses, including those that affect the spatial distribution of species. Lagged responses are frequent and species distributions and assemblages are consequently pushed into a disequilibrium state. How the characteristics of environmental change—for example, gradual ‘press’ disturbances such as rising temperatures due to climate change versus infrequent ‘pulse’ disturbances such as extreme events—affect the magnitude of responses and the relaxation times of biota has been insufficiently explored. It is also not well understood how widely used approaches to assess or project the responses of species to changing environmental conditions can deal with time lags. It, therefore, remains unclear to what extent time lags in species distributions are accounted for in biodiversity assessments, scenarios and models; this has ramifications for policymaking and conservation science alike. This perspective piece reflects on lagged species responses to environmental change and discusses the potential consequences for species distribution models (SDMs), the tools of choice in biodiversity modelling. We suggest ways to better account for time lags in calibrating these models and to reduce their leverage effects in projections for improved biodiversity science and policy.

Deep learning to extract the meteorological by‐catch of wildlife cameras - Jamie Alison; Stephanie Payne; Jake M. Alexander; Anne D. Bjorkman; Vincent Ralph Clark; Onalenna Gwate; Maria Huntsaar; Evelin Iseli; Jonathan Lenoir; Hjalte Mads Rosenstand Mann; Sandy‐Lynn Steenhuisen; Toke Thomas Høye (Global Change Biology, 2024)
Microclimate—proximal climatic variation at scales of metres and minutes—can exacerbate or mitigate the impacts of climate change on biodiversity. However, most microclimate studies are temperature centric, and do not consider meteorological factors such as sunshine, hail and snow. Meanwhile, remote cameras have become a primary tool to monitor wild plants and animals, even at micro‐scales, and deep learning tools rapidly convert images into ecological data. However, deep learning applications for wildlife imagery have focused exclusively on living subjects. Here, we identify an overlooked opportunity to extract latent, ecologically relevant meteorological information. We produce an annotated image dataset of micrometeorological conditions across 49 wildlife cameras in South Africa's Maloti‐Drakensberg and the Swiss Alps. We train ensemble deep learning models to classify conditions as overcast, sunshine, hail or snow. We achieve 91.7% accuracy on test cameras not seen during training. Furthermore, we show how effective accuracy is raised to 96% by disregarding 14.1% of classifications where ensemble member models did not reach a consensus. For two‐class weather classification (overcast vs. sunshine) in a novel location in Svalbard, Norway, we achieve 79.3% accuracy (93.9% consensus accuracy), outperforming a benchmark model from the computer vision literature (75.5% accuracy). Our model rapidly classifies sunshine, snow and hail in almost 2 million unlabelled images. Resulting micrometeorological data illustrated common seasonal patterns of summer hailstorms and autumn snowfalls across mountains in the northern and southern hemispheres. However, daily patterns of sunshine and shade diverged between sites, impacting daily temperature cycles. Crucially, we leverage micrometeorological data to demonstrate that (1) experimental warming using open‐top chambers shortens early snow events in autumn, and (2) image‐derived sunshine marginally outperforms sensor‐derived temperature when predicting bumblebee foraging. These methods generate novel micrometeorological variables in synchrony with biological recordings, enabling new insights from an increasingly global network of wildlife cameras.

Mouse phenome database: curated data repository with interactive multi-population and multi-trait analyses - Molly A. Bogue; Robyn L. Ball; David O. Walton; Matthew H. Dunn; Georgi Kolishovski; Alexander Berger; Anna Lamoureux; Stephen C. Grubb; Matthew Gerring; Matthew Kim; Hongping Liang; Jake Emerson; et al. (Mammalian Genome, 2023)
The Mouse Phenome Database continues to serve as a curated repository and analysis suite for measured attributes of members of diverse mouse populations. The repository includes annotation to community standard ontologies and guidelines, a database of allelic states for 657 mouse strains, a collection of protocols, and analysis tools for flexible, interactive, user directed analyses that increasingly integrates data across traits and populations. The database has grown from its initial focus on a standard set of inbred strains to include heterogeneous mouse populations such as the Diversity Outbred and mapping crosses and well as Collaborative Cross, Hybrid Mouse Diversity Panel, and recombinant inbred strains. Most recently the system has expanded to include data from the International Mouse Phenotyping Consortium. Collectively these data are accessible by API and provided with an interactive tool suite that enables users’ persistent selection, storage, and operation on collections of measures. The tool suite allows basic analyses, advanced functions with dynamic visualization including multi-population meta-analysis, multivariate outlier detection, trait pattern matching, correlation analyses and other functions. The data resources and analysis suite provide users a flexible environment in which to explore the basis of phenotypic variation in health and disease across the lifespan.

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Compensatory responses of vital rates attenuate impacts of competition on population growth and promote coexistence - Shengman Lyu; Jake M. Alexander (Ecology Letters, 2023)
Competition is among the most important factors regulating plant population and community dynamics, but we know little about how different vital rates respond to competition and jointly determine population growth and species coexistence. We conducted a field experiment and parameterised integral projection models to model the population growth of 14 herbaceous plant species in the absence and presence of neighbours across an elevation gradient (284 interspecific pairs). We found that suppressed individual growth and seedling establishment contributed the most to competition‐induced declines in population growth, although vital rate contributions varied greatly between species and with elevation. In contrast, size‐specific survival and flowering probability and seed production were frequently enhanced under competition. These compensatory vital rate responses were nearly ubiquitous (occurred in 92% of species pairs) and significantly reduced niche overlap and stabilised coexistence. Our study highlights the importance of demographic processes for regulating population and community dynamics, which has often been neglected by classic coexistence theories.

Ecological lags govern the pace and outcome of plant community responses to 21st‐century climate change - Sebastián Block; Marc‐Jacques Maechler; Jacob I. Levine; Jake M. Alexander; Loïc Pellissier; Jonathan M. Levine (Ecology Letters, 2022)
Forecasting the trajectories of species assemblages in response to ongoing climate change requires quantifying the time lags in the demographic and ecological processes through which climate impacts species' abundances. Since experimental climate manipulations are typically abrupt, the observed species responses may not match their responses to gradual climate change. We addressed this problem by transplanting alpine grassland turfs to lower elevations, recording species' demographic responses to climate and competition, and using these data to parameterise community dynamics models forced by scenarios of gradual climate change. We found that shifts in community structure following an abrupt climate manipulation were not simply accelerated versions of shifts expected under gradual warming, as the former missed the transient rise of species benefiting from moderate warming. Time lags in demography and species interactions controlled the pace and trajectory of changing species' abundances under simulated 21st‐century climate change, and thereby prevented immediate diversity loss.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Drivers of local extinction risk in alpine plants under warming climate - Hanna A. Nomoto; Jake M. Alexander (Ecology Letters, 2021)
The scarcity of local plant extinctions following recent climate change has been explained by demographic inertia and lags in the displacement of resident species by novel species, generating an ‘extinction debt’. We established a transplant experiment to disentangle the contribution of these processes to the local extinction risk of four alpine plants in the Swiss Alps. Projected population growth (λ) derived from integral projection models was reduced by 0.07/°C of warming on average, whereas novel species additionally decreased λ by 0.15 across warming levels. Effects of novel species on predicted extinction time were greatest at warming

Selective extinctions resulting from random habitat destruction lead to under‐estimates of local and regional biodiversity loss in a manipulative field experiment - Ryan J. Almeida; Alexander A. G. Berro; Alston Lippert; Jake Clary; Sam McKlin; Erin V. Scott; Kevin G. Smith (Global Change Biology, 2021)
Land‐use change is a significant cause of anthropogenic extinctions, which are likely to continue and accelerate as habitat conversion proceeds in most biomes. One way to understand the effects of habitat loss on biodiversity is through improved tools for predicting the number and identity of species losses in response to habitat loss. There are relatively few methods for predicting extinctions and even fewer opportunities for rigorously assessing the quality of these predictions. In this paper, we address these issues by applying a new method based on rarefaction to predict species losses after random, but aggregated, habitat loss. We compare predictions from three rarefaction models, individual‐based, sample‐based, and spatially clustered, to those derived from a commonly used extinction estimation method, the species–area relationship (SAR). We apply each method to a mesocosm experiment, in which we aim to predict species richness and extinctions of arthropods immediately following 50% habitat loss. While each model produced strikingly accurate predictions of species richness immediately after the habitat loss disturbance, each model significantly underestimated the number of extinctions occurring at both the local (within‐mesocosm) and regional (treatment‐wide) scales. Despite the stochastic nature of our small‐scale, short‐term, and randomly applied habitat loss experiment, we found surprisingly clear evidence for extinction selectivity, for example, when abundant species with low extinction probabilities were extirpated following habitat loss. The important role played by selective extinction even in this contrived experimental system suggests that ecologically driven, trait‐based extinctions play an equally important role to stochastic extinction, even when the disturbance itself has no clear selectivity. As a result, neutrally stochastic null models such as the SAR and rarefaction are likely to underestimate extinctions caused by habitat loss. Nevertheless, given the difficulty of predicting extinctions, null models provide useful benchmarks for conservation planning by providing minimum estimates and probabilities of species extinctions.

Macroecology in the age of Big Data – Where to go from here? - Rafael O. Wüest; Niklaus E. Zimmermann; Damaris Zurell; Jake M. Alexander; Susanne A. Fritz; Christian Hof; Holger Kreft; Signe Normand; Juliano Sarmento Cabral; Eniko Szekely; Wilfried Thuiller; Martin Wikelski; et al. (Journal of Biogeography, 2020)
Recent years have seen an exponential increase in the amount of data available in all sciences and application domains. Macroecology is part of this “Big Data” trend, with a strong rise in the volume of data that we are using for our research. Here, we summarize the most recent developments in macroecology in the age of Big Data that were presented at the 2018 annual meeting of the Specialist Group Macroecology of the Ecological Society of Germany, Austria and Switzerland (GfÖ). Supported by computational advances, macroecology has been a rapidly developing field over recent years. Our meeting highlighted important avenues for further progress in terms of standardized data collection, data integration, method development and process integration. In particular, we focus on (a) important data gaps and new initiatives to close them, for example through space‐ and airborne sensors, (b) how various data sources and types can be integrated, (c) how uncertainty can be assessed in data‐driven analyses and (d) how Big Data and machine learning approaches have opened new ways of investigating processes rather than simply describing patterns. We discuss how Big Data opens up new opportunities, but also poses new challenges to macroecological research. In the future, it will be essential to carefully assess data quality, the reproducibility of data compilation and analytical methods, and the communication of uncertainties. Major progress in the field will depend on the definition of data standards and workflows for macroecology, such that scientific quality and integrity are guaranteed, and collaboration in research projects is made easier.

Scaling the linkage between environmental niches and functional traits for improved spatial predictions of biological communities - Antoine Guisan; Heidi K. Mod; Daniel Scherrer; Tamara Münkemüller; Julien Pottier; Jake M. Alexander; Manuela D'Amen (Global Ecology and Biogeography, 2019)
Issue Approaches to predicting species assemblages through stacking individual niche‐based species distribution models (S‐SDMs) need to account for community processes other than abiotic filtering. Such constraints have been introduced by implementing ecological assembly rules (EARs) into S‐SDMs, and can be based on patterns of functional traits in communities. Despite being logically valid, this approach has led to a limited improvement in prediction, possibly because of mismatches between the scales of measurement of niche and trait data. Evidence S‐SDM studies have often related single values of a species’ traits to environmental niches that are captured by abiotic conditions measured at a much finer spatial scale, without accounting for intraspecific trait variation along environmental gradients. Many pieces of evidence show that omitting intraspecific trait variation can hinder the proper inference of EARs from trait patterns, and we further argue that it can therefore also affect our capacity to spatially predict functional properties of communities. In addition, estimates of environmental niches and trait envelopes may vary depending on the scale at which environmental and trait measurements are made. Conclusion We suggest that to overcome these limitations, surveys sampling both niche and trait measurements should be conducted at fine scales along wide environmental gradients, and integrated at the same scale to test and improve a new generation of spatial community models and their functional properties.

Running off the road: roadside non-native plants invading mountain vegetation - Keith L. McDougall; Jonas Lembrechts; Lisa J. Rew; Sylvia Haider; Lohengrin A. Cavieres; Christoph Kueffer; Ann Milbau; Bridgett J. Naylor; Martin A. Nuñez; Anibal Pauchard; Tim Seipel; Karina L. Speziale; et al. (Biological Invasions, 2018)

Mountain roads and non‐native species modify elevational patterns of plant diversity - Sylvia Haider; Christoph Kueffer; Helge Bruelheide; Tim Seipel; Jake M. Alexander; Lisa J. Rew; José Ramón Arévalo; Lohengrin A. Cavieres; Keith L. McDougall; Ann Milbau; Bridgett J. Naylor; Karina Speziale; et al. (Global Ecology and Biogeography, 2018)
Aim We investigated patterns of species richness and community dissimilarity along elevation gradients using globally replicated, standardized surveys of vascular plants. We asked how these patterns of diversity are influenced by anthropogenic pressures (road construction and non‐native species). Location Global. Time period 2008–2015. Major taxa studied Vascular plants. Methods Native and non‐native vascular plant species were recorded in 943 plots along 25 elevation gradients, in nine mountain regions, on four continents. Sampling took place in plots along and away from roads. We analysed the effects of elevation and distance from road on species richness patterns and community dissimilarity (beta‐diversity), and assessed how non‐native species modified such elevational diversity patterns. Results Globally, native and total species richness showed a unimodal relationship with elevation that peaked at lower‐mid elevations, but these patterns were altered along roads and due to non‐native species. Differences in elevational species richness patterns between regions disappeared along roadsides, and non‐native species changed the patterns’ character in all study regions. Community dissimilarity was reduced along roadsides and through non‐native species. We also found a significant elevational decay of beta‐diversity, which however was not affected by roads or non‐native species. Main conclusions Idiosyncratic native species richness patterns in plots away from roads implicate region‐specific mechanisms underlying these patterns. However, along roadsides a clearer elevational signal emerged and species richness mostly peaked at mid‐elevations. We conclude that both roads and non‐native species lead to a homogenization of species richness patterns and plant communities in mountains.

Lags in the response of mountain plant communities to climate change - Jake M. Alexander; Loïc Chalmandrier; Jonathan Lenoir; Treena I. Burgess; Franz Essl; Sylvia Haider; Christoph Kueffer; Keith McDougall; Ann Milbau; Martin A. Nuñez; Aníbal Pauchard; Wolfgang Rabitsch; et al. (Global Change Biology, 2018)
Rapid climatic changes and increasing human influence at high elevations around the world will have profound impacts on mountain biodiversity. However, forecasts from statistical models (e.g. species distribution models) rarely consider that plant community changes could substantially lag behind climatic changes, hindering our ability to make temporally realistic projections for the coming century. Indeed, the magnitudes of lags, and the relative importance of the different factors giving rise to them, remain poorly understood. We review evidence for three types of lag: “dispersal lags” affecting plant species’ spread along elevational gradients, “establishment lags” following their arrival in recipient communities, and “extinction lags” of resident species. Variation in lags is explained by variation among species in physiological and demographic responses, by effects of altered biotic interactions, and by aspects of the physical environment. Of these, altered biotic interactions could contribute substantially to establishment and extinction lags, yet impacts of biotic interactions on range dynamics are poorly understood. We develop a mechanistic community model to illustrate how species turnover in future communities might lag behind simple expectations based on species’ range shifts with unlimited dispersal. The model shows a combined contribution of altered biotic interactions and dispersal lags to plant community turnover along an elevational gradient following climate warming. Our review and simulation support the view that accounting for disequilibrium range dynamics will be essential for realistic forecasts of patterns of biodiversity under climate change, with implications for the conservation of mountain species and the ecosystem functions they provide.

A Framework for Evaluating Heterogeneity and Landscape-Level Impacts of Non-native Aquatic Species - M. Jake Vander Zanden; Gretchen J. A. Hansen; Alexander W. Latzka (Ecosystems, 2017)

Plant invasions into mountains and alpine ecosystems: current status and future challenges - Jake M. Alexander; Jonas J. Lembrechts; Lohengrin A. Cavieres; Curtis Daehler; Sylvia Haider; Christoph Kueffer; Gang Liu; Keith McDougall; Ann Milbau; Aníbal Pauchard; Lisa J. Rew; Tim Seipel (Alpine Botany, 2016)

Non-native and native organisms moving into high elevation and high latitude ecosystems in an era of climate change: new challenges for ecology and conservation - Aníbal Pauchard; Ann Milbau; Ann Albihn; Jake Alexander; Treena Burgess; Curtis Daehler; Göran Englund; Franz Essl; Birgitta Evengård; Gregory B. Greenwood; Sylvia Haider; Jonathan Lenoir; et al. (Biological Invasions, 2016)

Representing calcification in distribution models for aquatic invasive species: surrogates perform as well as CaCO3 saturation state - Alexander W. Latzka; John T. Crawford; Avery S. Koblings; Yuri Caldeira; Emily Hilts; M. Jake Vander Zanden (Hydrobiologia, 2015)

Performance of the herb Verbascum thapsus along environmental gradients in its native and non‐native ranges - Tim Seipel; Jake M. Alexander; Curtis C. Daehler; Lisa J. Rew; Peter J. Edwards; Pervaiz A. Dar; Keith McDougall; Bridgett Naylor; Catherine Parks; Fredric W. Pollnac; Zafar A. Reshi; Mel Schroder; et al. (Journal of Biogeography, 2015)
Aim We evaluated whether the performance of individuals and populations of the invasive plant Verbascum thapsus differs between its native and non‐native ranges, across climate gradients, and in response to its position in a global‐scaled niche model. Location India (Kashmir) and Switzerland (native range) and Australia and USA (Hawaii, Montana and Oregon) (non‐native range). Methods We measured population characteristics (density of flowering individuals, population size), plant traits (plant height, number of flowering branches) and seed germination for 50 populations of V. thapsus growing along elevational gradients in six mountain regions around the world (two in the native range, and four in the non‐native range). We fitted linear regression models to determine the relationship of plant and population level performance variables to range, region, climate and probability of occurrence from a global niche model. Results Plant height, number of flowering branches and population density of V. thapsus did not differ consistently between the native and non‐native ranges, but the area covered by populations in the non‐native range was on average two orders of magnitude larger than the area of native populations. Within and among regions, individual plant performance traits responded variably to precipitation and mean annual temperature, depending on the climatic range of the observed populations; however, performance was greater for populations that had a greater modelled probability of occurrence. Seed germination under controlled conditions was highest between 20 and 35 °C and consistent across populations, although germination at low temperatures was substantially higher for native populations from Kashmir. Main conclusions The introduction of V. thapsus to its non‐native range is not associated with consistent increases in plant performance. Instead, plant performance is more strongly influenced by position within the climate niche of the species, position along environmental gradients, and climatic or other differences among regions. We demonstrate that individual‐level and population‐level performance traits can yield different predictors of plant performance. Therefore, future studies comparing plant performance in native and non‐native ranges should include both plant and population characteristics and should also sample the target species from multiple regions in both ranges and along environmental gradients that comprehensively represent the niche of the species.

Evolutionary responses to global change: lessons from invasive species - Emily V. Moran; Jake M. Alexander (Ecology Letters, 2014)
Biologists have recently devoted increasing attention to the role of rapid evolution in species' responses to environmental change. However, it is still unclear what evolutionary responses should be expected, at what rates, and whether evolution will save populations at risk of extinction. The potential of biological invasions to provide useful insights has barely been realised, despite the close analogies to species responding to global change, particularly climate change; in both cases, populations encounter novel climatic and biotic selection pressures, with expected evolutionary responses occurring over similar timescales. However, the analogy is not perfect, and invasive species are perhaps best used as an upper bound on expected change. In this article, we review what invasive species can and cannot teach us about likely evolutionary responses to global change and the constraints on those responses. We also discuss the limitations of invasive species as a model and outline directions for future research.

How comparable are species distributions along elevational and latitudinal climate gradients? - Aud H. Halbritter; Jake M. Alexander; Peter J. Edwards; Regula Billeter (Global Ecology and Biogeography, 2013)
Aim Because climatic factors, especially temperature, show similar trends with elevation and latitude, it is often assumed that elevational gradients can be used as a proxy for understanding ecological processes along latitudinal gradients. We investigated the validity of this assumption for herbaceous plants, testing the hypotheses that (1) species reach the same climate limits, and (2) exhibit similar distribution patterns along both types of gradient. Location S wiss A lps and S candinavia. Methods We recorded the occurrence of 155 ruderal plant species along an elevational gradient in the Swiss Alps and a latitudinal gradient, both reaching beyond the distribution limit of most species. Principal components analysis was used to summarize climatic variation in temperature and precipitation across these gradients and assessed the relationship across species between climatic limits along the two gradients. We used logistic regressions to compare how the probability of occurrence of individual species changed with climate along the two gradients. Results We found no correlation of species principal components analysis ( PCA ) values (climate limit) along an elevational and latitudinal precipitation gradient ( PC1 ) but a positive correlation along a temperature gradient ( PC2 ). Species reached a colder climate limit (on average 244 growing degree days lower) and decreased in occurrence more gradually along the elevational compared to the latitudinal gradient. Main conclusions We suggest that the differences in distribution patterns and limits along similar climatic gradients are mainly due to the much shorter dispersal distances along elevational than latitudinal gradients, although other explanations are also possible. We can therefore expect plants in mountains and lowland regions to respond differently to rapid climate change, and so caution must be exercised when using elevation as a proxy for latitude in studies of species distribution. Nonetheless, comparative studies along such gradients can yield important insights into the factors that limit species distributions.

Change in a lake benthic community over a century: evidence for alternative community states - Alexander Y. Karatayev; Lyubov E. Burlakova; M. Jake Vander Zanden; Richard C. Lathrop; Dianna K. Padilla (Hydrobiologia, 2013)

Genetically based differentiation in growth of multiple non-native plant species along a steep environmental gradient - Sylvia Haider; Christoph Kueffer; Peter J. Edwards; Jake M. Alexander (Oecologia, 2012)

The invasion of plant communities following extreme weather events under ambient and elevated temperature - Christine S. Sheppard; Jake M. Alexander; Regula Billeter (Plant Ecology, 2012)

Processes at multiple scales affect richness and similarity of non‐native plant species in mountains around the world - Tim Seipel; Christoph Kueffer; Lisa J. Rew; Curtis C. Daehler; Aníbal Pauchard; Bridgett J. Naylor; Jake M. Alexander; Peter J. Edwards; Catherine G. Parks; José Ramon Arevalo; Lohengrin A. Cavieres; Hansjörg Dietz; et al. (Global Ecology and Biogeography, 2012)
Aim To investigate how species richness and similarity of non‐native plants varies along gradients of elevation and human disturbance. Location Eight mountain regions on four continents and two oceanic islands. Methods We compared the distribution of non‐native plant species along roads in eight mountainous regions. Within each region, abundance of plant species was recorded at 41–84 sites along elevational gradients using 100‐m 2 plots located 0, 25 and 75 m from roadsides. We used mixed‐effects models to examine how local variation in species richness and similarity were affected by processes at three scales: among regions (global), along elevational gradients (regional) and with distance from the road (local). We used model selection and information criteria to choose best‐fit models of species richness along elevational gradients. We performed a hierarchical clustering of similarity to investigate human‐related factors and environmental filtering as potential drivers at the global scale. Results Species richness and similarity of non‐native plant species along elevational gradients were strongly influenced by factors operating at scales ranging from 100 m to 1000s of km. Non‐native species richness was highest in the New World regions, reflecting the effects of colonization from Europe. Similarity among regions was low and due mainly to certain Eurasian species, mostly native to temperate Europe, occurring in all New World regions. Elevation and distance from the road explained little of the variation in similarity. The elevational distribution of non‐native species richness varied, but was always greatest in the lower third of the range. In all regions, non‐native species richness declined away from roadsides. In three regions, this decline was steeper at higher elevations, and there was an interaction between distance and elevation. Main conclusions Because non‐native plant species are affected by processes operating at global, regional and local scales, a multi‐scale perspective is needed to understand their patterns of distribution. The processes involved include global dispersal, filtering along elevational gradients and differential establishment with distance from roadsides.

The role of bioclimatic origin, residence time and habitat context in shaping non-native plant distributions along an altitudinal gradient - Sylvia Haider; Jake Alexander; Hansjörg Dietz; Ludwig Trepl; Peter J. Edwards; Christoph Kueffer (Biological Invasions, 2010)

Genetic differences in the elevational limits of native and introduced Lactuca serriola populations - Jake M. Alexander (Journal of Biogeography, 2010)
Aim Differences in phenological timing might explain why populations of the annual Lactuca serriola reach higher elevational limits in a part of its introduced range than in its native range. I investigated (1) whether this difference in elevational limits has a genetic basis, (2) the importance of clinal genetic differentiation and phenotypic plasticity in phenology as responses to elevation in L. serriola , and whether these responses differ between regions, and (3) whether the realized temperature niche of L. serriola differs between the two regions. Location Plant material was collected in Canton Valais, Switzerland (native range) and the Wallowa Mountains, Oregon, USA (introduced range). The field experiment was conducted in Canton Grisons, Switzerland. Methods Plants from 20 populations collected along elevational gradients were grown in eight common gardens established at 200‐m elevational intervals (600–2000 m a.s.l.). The timing of phenological transitions was monitored and analysed with mixed‐effects models to determine differences in (1) elevational limits, and (2) clinal genetic differentiation and phenotypic plasticity as responses to elevation for plants from each region. The limits of the species along five temperature gradients were derived from generalized linear models using published occurrence data to quantify regional differences in the realized temperature niche. Results The limit of seed set (1400 m a.s.l.) was the same for plants of both regions. However, the limit of flowering, probably a better reflection of elevational limits in this study, was 400 m higher for plants from the introduced region due to their faster development. Native populations showed clines in development time with elevation consistent with expectations. However, these were weaker in introduced populations, the responses of which were rather characterized by phenotypic plasticity. Thus, although introduced populations grow at considerably cooler sites than in the native region, this is unlikely to have resulted from direct selection for tolerance of high‐elevation conditions. Main conclusions This study supports a genetic basis for differences in the elevational limits of L. serriola populations between two parts of its native and introduced range. Although it is not yet clear whether these differences evolved in the introduced range, these findings highlight the potential of alien species for gaining insights into niche evolution.

Establishment of parallel altitudinal clines in traits of native and introduced forbs - Jake M. Alexander; Peter J. Edwards; Myriam Poll; Catherine G. Parks; Hansjörg Dietz (Ecology, 2009)
Due to altered ecological and evolutionary contexts, we might expect the responses of alien plants to environmental gradients, as revealed through patterns of trait variation, to differ from those of the same species in their native range. In particular, the spread of alien plant species along such gradients might be limited by their ability to establish clinal patterns of trait variation. We investigated trends in growth and reproductive traits in natural populations of eight invasive Asteraceae forbs along altitudinal gradients in their native and introduced ranges (Valais, Switzerland, and Wallowa Mountains, Oregon, USA). Plants showed similar responses to altitude in both ranges, being generally smaller and having fewer inflorescences but larger seeds at higher altitudes. However, these trends were modified by region‐specific effects that were independent of species status (native or introduced), suggesting that any differential performance of alien species in the introduced range cannot be interpreted without a fully reciprocal approach to test the basis of these differences. Furthermore, we found differences in patterns of resource allocation to capitula among species in the native and the introduced areas. These suggest that the mechanisms underlying trait variation, for example, increasing seed size with altitude, might differ between ranges. The rapid establishment of clinal patterns of trait variation in the new range indicates that the need to respond to altitudinal gradients, possibly by local adaptation, has not limited the ability of these species to invade mountain regions. Studies are now needed to test the underlying mechanisms of altitudinal clines in traits of alien species.